An Analytical Study on the Assessment of Planning, Implementation, Control and Financing - Hummidi, Buthaina Rashed (Opción, 2019)
This study aims to examine the federal budget of Iraq and the general budget of the state for the period of 2009 to 2016 with the exception of 2014 via analytical and comparison method. It has resulted that the proportion of expenditure of most ministries for the period (2009-2016) investigated was stable, with most ministries receiving very close percentages. As a conclusion, the investment proportion and budget on education was very small and the assessment of universities globally depends primarily on the infrastructure of university such as laboratory and well-equipped halls with modern technologies.